The populist allure of social media activism: Individualized charismatic authority. (May 2020) - Gustafsson, Nils; Weinryb, Noomi
This article argues that the type of individualized social media activism that has been conceptualized as 'connective action' has affinities to populism, and may have detrimental consequences for democratic procedures and the bureaucratic structures that enable them. We trace the normative allure of individualized digital engagement to the libertarian roots of techno-utopianism and argue that this, in combination with a form of mobilization fueled by digital enthusiasm, has potentially dire democratic and organizational consequences. Digital enthusiasm generated on social media platforms entails self-infatuation, here conceptualized as a form of individualized charismatic authority in the Weberian sense. This individualized form of charismatic authority is fundamentally focused on personalized engagement, and simultaneously interconnected through the technological affordances of social media platforms. If individualized charismatic authority becomes institutionalized as a legitimate and predominant manner of organizing, it may have large-scale implications for societal organizing at large by promoting populism. In sum, we argue that digital enthusiasm not only provides democratic opportunities for protest and contention in civil society, but that the fickleness of the individualized charismatic authority it generates may also put democratic procedures and respect for bureaucratic structures at risk.